2017
DOI: 10.1145/3134666
|View full text |Cite
|
Sign up to set email alerts
|

You Can't Stay Here

Abstract: In 2015, Reddit closed several subreddits-foremost among them r/fatpeoplehate and r/CoonTown-due to violations of Reddit's anti-harassment policy. However, the effectiveness of banning as a moderation approach remains unclear: banning might diminish hateful behavior, or it may relocate such behavior to different parts of the site. We study the ban of r/fatpeoplehate and r/CoonTown in terms of its effect on both participating users and affected subreddits. Working from over 100M Reddit posts and comments, we ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(98 citation statements)
references
References 20 publications
0
97
0
1
Order By: Relevance
“…The topic of understanding online human behavior has been of a great interest to CSCW/HCI researchers in various contexts such as mental health [19,23], political polarization [11,35], and abusive social behaviors [13,50]. Our findings challenge the assumption often made by such studies that online social media content is always created by humans.…”
Section: Discussionmentioning
confidence: 44%
“…The topic of understanding online human behavior has been of a great interest to CSCW/HCI researchers in various contexts such as mental health [19,23], political polarization [11,35], and abusive social behaviors [13,50]. Our findings challenge the assumption often made by such studies that online social media content is always created by humans.…”
Section: Discussionmentioning
confidence: 44%
“…A study on Slashdot -a popular website with a good amount of moderation -found that users come to a consensus about the community's moderation policies and such moderation practices enable large scale civil participation [53]. Reddit's decision to ban hate communities resulted in a reduction of abusive language [16]. An analysis of different moderation styles in online health support communities found that positive and rewarding moderation styles are more effective than negative and punishing styles [58].…”
Section: Effects Of Norm Enforcementmentioning
confidence: 99%
“…We use these nine lexicons in addition to the words from Wikipedia manual. 16 A list of all the lexicons we used is shown in Table 1 with a description, sources, and example terms. To characterize the amount of biased language in a text, we compute the coverage of each lexicon words per token in the text.…”
Section: Identifying Biased Languagementioning
confidence: 99%
See 2 more Smart Citations